Proceeding of The 13th International Conference onMalaysia-Indonesia Relations (PAHMI). Contributions of Humanities and Social Sciences on the Direction of Malay Studies in the Era of Industry 4.0 - Sawirman (De Gruyter, 2019)
Description This conference is aimed at promoting deeper understanding and relations between Malaysia and Indonesia at an academic, inter-societal and non-state level. It also seeks to encourage cooperation between researchers, academic institutions, civil society organizations and individuals in both countries, stimulating dialogue on the bilateral relations and common interests of both countries, regionally and globally. Aims and Scope HUMANITIES AND THE ARTS Human and Environment, Cultural Identities, Cultural Diversities, Intercultural Relations, Cultural Heritage, Cultural Studies, Research into the Humanities SOCIAL STUDIES AND POLITICS Border and Migration, History, Memory and Politics, Social and Communities Study, Civic and Political Studies, Global Studies, Research into the Social Science RELATED STUDIES Environmental Studies, Human and Technology Education, Media and Technology, Global Economics Instructions for Authors As an author, it is crucial to follow the guidelines and formatting instructions to prepare and submit your paper in order to have it published in proceedings. Before submitting the paper, please use the conference template which can be found in the the website: http://pahmi13.conference.unand.ac.id/ Each individual is limited to one personal appearance on the programme as a presenting author. This policy precludes acceptance of papers for more than one presentation. In other words, an author can submit and present only one paper. However, a presenter can always be a non-presenting co-author on additional papers. Please read the instructions carefully prior to submitting: Each paper can only be submitted to ONE track. Submitted papers must NOT have been previously published and if under review, must NOT appear in othe